Adaptation of beans to infertile soils - Lynch, J; Piha, M (Southern Africa Development Coordination Conference (SADCC), 1988)
Beans do not appear inherently suited to infertile soils. A diagnostic effort to define and evaluate soil constraints in African bean production is needed. We suggest bean BNF is host- plant limited, and that BNF in short-season bean is due to inadequate C and N dynamics in the bean plant. In infertile soils, improved host-plant resistance to edaphic stresses may improve BNF. Several studies indicate that heritable variation exists in bean with regard to resistance to low soil P. Additional promising avenues of research on resistance to low soil P include mycorrhizal symbiosis, rhizosphere modification and root morphology. For nutritional characteristics, specific physiological traits may be more fruitful selection criteria than plant vigour and yield. Mechanistic research on Ca deficiency, Al toxicity and P deficiency would be useful in defining traits to be used in breeding improved bean materials for infertile African soils. (AS)